Profile of herbal and dietary supplements induced liver injury in Latin America: A systematic review of published reports - Santos, Genario; Gasca, Jessica; Parana, Raymundo; Nunes, Vinicius; Schinnoni, Maria; Medina-Cáliz, Inmaculada; Cabello-Porras, María Rosario; Lucena-González, María Isabel; Andrade-Bellido, Raúl Jesús (WILEY, 2020)
Hepatotoxicity related to HDS is a growing global health issue. We have undertaken a systematic review of published case reports and case series from LA from 1976 to 2020 to describe the clinical features of HDS related hepatotoxicity in this region. We search in PubMed, Web of Science, Scopus and specific LA databases according to PRISMA guidelines. Only HILI cases published in LA that met criteria for DILI definition were included. Duplicate records or reports that lacked relevant data that precluded establishing causality were excluded. Finally, 17 records (23 cases) were included in this review. Centella asiatica, Carthamus tinctorius, and Herbalife® were the most reported HDS culprit products, the main reason for HDS consumption was weight loss. The clinical characteristics of HDS hepatotoxicity in our study were compared to those of other studies in the USA, Europe and China showing a similar signature with predominance of young females, hepatocellular damage, a high rate of ALF and mortality, more frequent inadvertent re-challenge and chronic damage. This study underscores the challenge in causality assessment when multi-ingredients HDS are taken and the need for consistent publication practice when reporting hepatotoxicity cases due to HDS, to foster HDS liver safety particularly in LA.
Keywords: Hígado - Enfermedades - América latina; Suplementos nutricionales - Toxicología - América latina; Latin America; Hepatotoxicity; Herbal and dietary supplements-induced liver injury; Outcome; Phenotypic presentations